2021
DOI: 10.1098/rspb.2020.3145
|View full text |Cite
|
Sign up to set email alerts
|

Maximum CO2diffusion inside leaves is limited by the scaling of cell size and genome size

Abstract: Maintaining high rates of photosynthesis in leaves requires efficient movement of CO 2 from the atmosphere to the mesophyll cells inside the leaf where CO 2 is converted into sugar. CO 2 diffusion inside the leaf depends directly on the structure of the mesophyll cells and their surrounding airspace, which have been difficult to characterize because of their inherently three-dimensional organization. Yet faster CO 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 64 publications
1
83
1
2
Order By: Relevance
“…We present this example because Buckley (2015) developed a model to estimate horizontal and vertical water transport in both the spongy and palisade regions, and the model would benefit from having the random walk observations incorporated. Our data show that vertical movement is less tortuous than horizontal movement in both the palisade and spongy mesophyll and overall the palisade mesophyll is more tortuous than the spongy mesophyll, result that parallel modelled g ias and g liq for both spongy and palisade mesophyll across the plant phylogeny (Théroux-Rancourt et al, 2021). Our understanding of water transport could also be enhanced by combining S mc , S m and directional tortuosity.…”
Section: The Value Of Directional Tortuositymentioning
confidence: 56%
See 1 more Smart Citation
“…We present this example because Buckley (2015) developed a model to estimate horizontal and vertical water transport in both the spongy and palisade regions, and the model would benefit from having the random walk observations incorporated. Our data show that vertical movement is less tortuous than horizontal movement in both the palisade and spongy mesophyll and overall the palisade mesophyll is more tortuous than the spongy mesophyll, result that parallel modelled g ias and g liq for both spongy and palisade mesophyll across the plant phylogeny (Théroux-Rancourt et al, 2021). Our understanding of water transport could also be enhanced by combining S mc , S m and directional tortuosity.…”
Section: The Value Of Directional Tortuositymentioning
confidence: 56%
“…At the time Roderick et al (1999) lamented that there was 'currently no simple means to measure the volume of solution or structure within a leaf', a situation that has been remedied in the intervening time including by this paper. Considering leaf construction economics begins to explain why leaves appear not to have 'perfect' anatomical arrangements that optimize CO 2 and H 2 O exchange and will be an important factor when interpreting 3D leaf anatomy data (Deans, Brodribb, Busch, & Farquhar, 2020;Lundgren & Fleming, 2020;Théroux-Rancourt et al, 2021).…”
Section: Cell Wall Propertiesmentioning
confidence: 99%
“…CaOx crystals contained in vascular bundle sheaths and other tissues such as sclerenchyma, collenchyma, or parenchyma, could also scatter light comprising a key component in the homogenization of the light gradient profile along the depth within the mesophyll [ 103 ] (see also Section 3.3 and Section 3.4 , below). Microscopic observations confirmed that the spatial distribution of the CaCIs is compatible with their proposed optical function [ 94 ]. Moreover, CaOx crystals within the epidermis of Lithops aucampiae leaves may scatter light within the below-ground region of the leaves, thus enriching the lower tissues with photons [ 59 ].…”
Section: Mesophyll Structural Elements Allow Efficient Light Propagation and Internal Light Homogenizationmentioning
confidence: 62%
“…The spongy cells are irregularly shaped, forming large intercellular air spaces that result in a greater effective light path lengthening and, subsequently, increased light absorption through multiple light scattering as the photons encounter numerous air–cell wall interfaces [ 90 , 91 , 92 , 93 ]. This anatomy also allows for the effective diffusion of CO 2 from the stomata, usually located at the abaxial epidermis in bifacial leaves, to the upper palisade layer where the larger proportion of photosynthesis takes place [ 94 ].…”
Section: Mesophyll Structural Elements Allow Efficient Light Propagation and Internal Light Homogenizationmentioning
confidence: 99%
“…Previous work has shown that mesophyll surface area per leaf area (S m ; µm 2 µm À2 ) has a strong influence on maximum photosynthesis (Nobel et al, 1975;Smith & Nobel, 1977). More recently, it has been suggested that the surface area of the mesophyll exposed to the IAS per unit of mesophyll volume (SA mes /V mes ; µm 2 µm À3 ) can influence plant photosynthetic performance given that the mesophyll-IAS boundary is the primary interface between the atmosphere and the photosynthetic cells (Earles et al, 2018;Th eroux-Rancourt et al, 2021). Other volumetric anatomical traits such as mesophyll porosity (i.e.…”
Section: Introductionmentioning
confidence: 99%